Chess square table / Amy Saiful Affendy Azhar Ahmad - Azhar Ahmad, Amy Saiful Affendy (Faculty of Applied Sciences, Universiti Teknologi MARA, Pahang, 2016)
Alternative source for furniture materials is needed due to the depleting supplies of raw materials (solid wood) for furniture industry. Machining wood waste is one possible solution to overcome this situation. In this study, a "Chess Square Table" was designed and produced by using machining wood waste and plywood. The price of the product must be at economical price. After design and manufacturing process, a survey was undertaken in evaluating the characteristics of the product based on gender, profession and range of age. The characteristics evaluated by the correspondents were such as suitability of raw materials used, suitability towards consumers, reducing machining wood waste, aesthetical value, ergonomics and anthropometrics design, price, and commercialization of the product. A set of questionnaires was distributed to 60 correspondents which consist of students, staffs, and furniture retailers. From the result, it shows that there are no significant different between the evaluation of the product's characteristics based on gender, profession, and range of age. It can be concluded that "Chess Square Table" was successfully designed and produced by using machining wood waste and plywood, at economical price. Hence, it also has great potential to be commercialized.